Wetlands management in Vietnam issues and perspectives. - Torell, M.; Salamanca, A.M.; Ratner, B.D. (eds. (Penang, Malaysia WorldFish Center, 2003)
WorldFish Center Tech. Rep. ( 61)
Keywords: Wetlands management; Wetlands conservation; Wetlands ecology